(untitled) (Journal of Engineering, 2023)
This work studies the impact of input machining parameters of Electrical Discharge Machining (EDM) on the machining process performance. Tool steel O1 was selected as the workpiece material, copper as the electrode material, and kerosene as the dielectric medium. Experimental runs have been carried out with a Design of Experiment (DOE) technique. Twenty tests are accomplished with the current range of (18 to 24 Ampere), a pulse duration range of (150 to 200 µs), and a pulse-off time range of (25 to 75 µs). Based upon the experimental study’s output results, the EDM parameter’s effect (voltage of power supply, discharge current, pulse duration, and pulse pause interval) on the responses of the process represented by surface roughness value Ra and Metal Removal MR rate. The results obtained by the DOE approach are analyzed by STATISTICA software. It has been concluded that an increase in the current and pulse duration maximizes both metal removal rate and surface roughness. At the same time, they are minimized by maximizing the pulse pause interval.